2019
DOI: 10.30863/didaktika.v13i1.340
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostik Kesulitan Belajar Matematika Siswa Sekolah Dasar Pada Materi Operasi Hitung Bilangan Bulat Negatif

Abstract: This study is qualitative research that aims to describe and analyze the students’ learning difficulties in mathematical operations of negative integers. The subjects of the study were two students of 286 SDN 286 Pasaka. Giving test (diagnostic tests) and interviewing were conducted to collect the data. The results of the study show that basically the learning difficulties experienced by the subject IS and subject RV is the same: the lack of understanding of the concept of negative integer operations. Due to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
16

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 0 publications
0
3
0
16
Order By: Relevance
“…Begitupun sebaliknya apabila materi dasar tidak dikuasai maka siswa akan menghadapi hambatan atau kesulitan dalam memahami pelajaran ditingkat yang lebih tinggi (Wulandari & Gusteti, 2020). Akibat Hambatan ini orang tersebut mengalami kegagalan atau tidak tercapainya tujuan pembelajaran tersebut (Nurjannah et al, 2019).…”
Section: Pendahuluanunclassified
“…Begitupun sebaliknya apabila materi dasar tidak dikuasai maka siswa akan menghadapi hambatan atau kesulitan dalam memahami pelajaran ditingkat yang lebih tinggi (Wulandari & Gusteti, 2020). Akibat Hambatan ini orang tersebut mengalami kegagalan atau tidak tercapainya tujuan pembelajaran tersebut (Nurjannah et al, 2019).…”
Section: Pendahuluanunclassified
“…Matematika dipelajari hampir di setiap jenjang pendidikan, bahkan sampai pada tingkat Perguruan Tinggi hingga sampai dunia kerja matematika pun masih merupakan sebuah kebutuhan ilmu (Fitriani, 2016). Pembelajaran matematika merupakan salah satu mata pelajaran yang wajib dipelajari oleh peserta didik disetiap jenjang pendidikan (Fitriani & Nurjannah, 2019). Namun matematika sering dianggap sulit bagi peserta didik.…”
Section: Pendahuluanunclassified
“…Kesulitan belajar matematika pada siswa berhubungan dengan kemampuan belajar yang kurang sempurna. Kekurangan tersebut dapat terungkap dari penyelesaian persoalan matematika yang tidak tuntas atau tuntas tetapi salah (Nurjannah, Danial, & Fitriani, 2019). Keberhasilan pembelajaran matematika dapat dilihat dari prestasi belajar matematika dan kemampuan lain yang mendukung prestasi tersebut (Nurul Iman, 2020).…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…The study of rational numbers is a subject of junior high school students. The study found that when learning the addition and subtraction of negative numbers, it is difficult for students to understand the concept of "negative to negative [7][8].…”
Section: Introductionmentioning
confidence: 99%